A systematic review and meta-analysis of influencing factors of postoperative wound healing in patients with anal fistula (肛瘘患者术后伤口愈合影响因素系统评价与Meta分析) - CHEN Qi (陈祺); LIU Zhiping (刘志平); BAI Jianying (白建英); LIU Bo (刘博); FENG Jiangxu (冯江雪) (中西医结合护理)
Objective To systematically evaluate the influencing factors of wound healing in patients undergoing anal fistula surgery, and to provide a theoretical basis for the formulation of reasonable treatment and nursing measures in clinical practice. Methods The computer searched CNKI, Wanfang, VIP Chinese Database, Pubmeide, Enbas, Weber Benschens and Techco Kranali Liberi English databases to collect clinical studies related to the influencing factors of anal fistula wound healing. Studies on the effect of the influencing factors of wound healing in patients undergoing anal fistula surgery were retrieved from CNKI, Wanfang database, VIP database, PubMed, Embase, Web of Science database and The Cochrane Library from the establishment to March 2024. Two trained researchers extracted relevant information according to the inclusion and exclusion criteria, and conducted the Meta-analysis using Revman5. 4 software. Results A total of 19 studies with a total of 2684 patients were included, with a score of ≥6. The results of meta-analysis showed that age ≥60 years old［OR=4. 87, 95%CI (2. 41, 9. 82), P＜0. 001］, alcohol consumption ［OR=0. 19, 95%CI (0. 11, 0. 28), P<0. 001］, BIM < 18. 5 kg/m2 ［OR=4. 99, 95%CI (3. 49, 7. 15), P＜0. 05］, diabetes mellitus ［OR=4. 32, 95%CI (2. 26, 8. 25), P＜0. 001］, anal fistula duration > 6 months ［OR=5. 38, 95%CI (2. 18, 13. 29), P＜0. 05］, complex anal fistula ［OR=5. 38, 95%CI (2. 18, 13. 29), P＜0. 001］, constipation ［OR=3. 50, 95%CI (2. 46, 4. 98), P＜0. 001］, poor stool quality ［OR=4. 88, 95%CI (3. 09, 7. 69), P＜0. 001］, wound postoperative infection ［OR=3. 60, 95%CI (2. 45, 5. 30), P＜0. 001］ and poor wound drainage ［OR=5. 69, 95%CI (2. 50, 12. 97), P＜0. 05］ were independent influencing factors for wound healing in patients with anal fistula after surgery. Conclusion Age(≥60 years old), alcohol consumption, diabetes, anal fistula duration > 6 months, complex anal fistula, constipation, poor stool quality, postoperative wound infection, and poor wound drainage were the influencing factors of postoperative wound healing in patients with anal fistula. This can be used as a reference to strengthen the perioperative assessment and nursing of patients with anal fistula and reduce the incidence of recurrence. (目的 系统评价肛瘘术后患者伤口愈合的影响因素, 为临床制定合理的护理措施提供理论依据。方法 计算机检索中国知网(CNKI)、万方(Wanfang Data)、维普中文数据库(VIP) 、 PubMed、EMbase、Web of Science和 The Cochrane Library英文数据库, 收集影响肛瘘术后伤口愈合相关因素的临床研究。检索时限均为建库至2024年3月。两名研究者独立筛选文献、提取资料并评价纳入文献的偏倚风险后, 采用RevMan5. 4软件进行系统评价。结果 纳入19篇文献, 共2684例患者, 纳入文献评价均≥6分。Meta分析结果显示: 年龄≥60岁［OR=4. 87, 95%CI(2. 41, 9. 82), P＜0. 001］、饮酒［OR=0. 19, 95%CI(0. 11, 0. 28), P＜0. 001］、BMI＜18. 5 kg/m2［OR=4. 99, 95%CI(3. 49, 7. 15), P＜0. 05］、糖尿病［OR=4. 32, 95%CI(2. 26, 8. 25), P＜0. 001］、肛瘘病程＞6个月［OR=3. 23, 95%CI(1. 94, 5. 37), P＜0. 05］、复杂肛瘘［OR=5. 38, 95%CI(2. 18, 13. 29), P＜0. 001］、便秘［OR=3. 50, 95%CI(2. 46, 4. 98), P＜0. 001］、大便性状欠佳［OR=2. 88, 95%CI(1. 80, 4. 33), P＜0. 001］、创面术后感染［OR=3. 60, 95%CI(2. 45, 5. 30), P＜0. 001］、创面引流不畅［OR=5. 69, 95%CI(2. 50, 12. 97), P＜0. 05］为肛瘘患者术后患者伤口愈合的的独立影响因素。结论 年龄≥60岁、饮酒、糖尿病、肛瘘病程＞6个月、复杂肛瘘、便秘、大便性状欠佳、创面术后感染、创面引流不畅是肛瘘患者术后伤口愈合的影响因素。可以此为参考, 加强肛瘘患者围术期评估与护理, 降低复发率发生率。)